U–Pb ages of granitoids around the Kofu basin: Implications for the Neogene geotectonic evolution of the South Fossa Magna region, central Japan. (6th August 2020) - Sawaki, Yusuke; Asanuma, Hisashi; Abe, Mariko; Hirata, Takafumi
Abstract: The Japanese archipelago underwent two arc–arc collisions during the Neogene. Southwest Honshu arc collided with the Izu‐Bonin‐Mariana arc and the northeast Honshu arc collided with the Chishima arc. The complicated geological structure of the South Fossa Magna region has been attributed to the collision between the Izu‐Bonin‐Mariana arc and the southwest Honshu arc. Understanding the geotectonic evolution of this tectonically active region is crucial for delineating the Neogene tectonics of the Japanese archipelago. Many intrusive granitoids occur around the Kofu basin, in the South Fossa Magna region. Although the igneous ages of these granitoids have been mainly estimated through biotite and hornblende K–Ar dating, here, we perform U–Pb dating of zircon to determine the igneous ages more precisely. In most cases, the secondary post‐magmatic overprint on the zircon U–Pb system was minor. Based on our results, we identify four groups of U–Pb ages: ca 15.5 Ma, ca 13 Ma, ca 10.5 Ma, and ca 4 Ma. The Tsuburai pluton belongs to the first group, and its age suggests that the granite formation within the Izu‐Bonin‐Mariana arc dates back to at least 15.5 Ma. The granitoids of the second group intruded into the boundary between the Honshu arc and the ancient Izu‐Bonin‐Mariana arc, suggesting that the arc–arc collision started by ca 13 Ma. As in the case of the Kaikomagatake pluton, the Chino pluton likely corresponds to a granodiorite formed in a rear‐arc setting in parallel with the other granodiorites of the third group. The U–Pb age of the Kogarasu pluton, which belongs to the fourth group, is the same as those of the Tanzawa tonalitic plutons. This might support a syncollisional rapid granitic magma formation in the South Fossa Magna region.